Förbättring av verkningsgraden i ett induktivt laddningssystem genom design av ny växelriktare - Hultin, Adam; Holm, Anton; Petersson, Lars; Tisell, Carl; Stelin, Johan; Thorslund, Anton (My University, 2015)
The purpose of the project which has been carried out at the department of Energy & Environment, division of Electric Power Engineering, has been to improve an already existing wireless charging system for an electric go-kart. The goal has been to improve the efficiency to 85% when 6 kW is fed to the system as well as to develop a control system that will enable charging without human supervision. The work process has consisted of: performing measurements, making theoretical calculations on power losses as well as designing a new power inverter. More essential parts of the power inverter have been tested on a breadboard. Subsequently a power inverter has been constructed and the result has been evaluated by measurements of the system. The result is a modified charging system where the efficiency for lower power levels has been improved through the construction of a new power inverter based on silicon carbide MOSFETs. However, the efficiency at 6 kW could not be established due to an unknown error in the power inverter which prevented measurements on higher power levels. Charging of the battery without human supervision has been made possible through the implementation of a control system.
Keywords: Elkraftteknik; Electric power engineering